The Landscape of Catastrophic Loss - Jeftanovic-Avdaloff, A (INDIANA UNIV PRESS, 2021)
Our biases and personal experiences inform our view of the world. Literature creates an alternative reality, and our memories of life s experiences help us create an entirely different universe. We are inclined to put together the pieces we want to remember, and these become our individual memory. Our perceptions of events and the ways we read them depend greatly on whether we live them as adults or in our formative years. Selective memory may have a healing effect or may torment us with images that won t go away. This personal essay explores how members of the second generation endeavor to work around the "black holes" in their family memories, where references, dates and information has been lost or erased as a result of political violence and traumatic experiences. Using some fiction and non-fictional texts as examples, I examine the ways in which I have constructed my identity, heritage and literary work.